Poster abstracts. (1st September 2013) - Wecht, Jill M.; Ivan, Adrian M.; Radulovic, Miroslav; Yen, Christina; Pena, Stephanie; Bauman, William A.; Ivan, Adrian M.; Radulovic, Miroslav; Rosado-Rivera, Dwindally; Yen, Christina; Bauman, William A.; Wecht, Jill M.; et al.
Abstract : Background We have demonstrated comparable increases in blood pressure (BP) after administration of midodrine and L-NAME during laboratory assessments in individuals with spinal cord injury (SCI). However, effects of these anti-hypotensive agents on 24-hour hemodynamics in those with SCI compared to intact able-bodied (AB) controls have not been reported. Objective To determine average (avg), minimum (min), and maximum (max) 24-hour systolic BP (SBP) diastolic BP (DBP) and heart rate (HR) responses in individuals with SCI and controls following administration of (1) midodrine hydrochloride (10 mg), (2) a nitric oxide synthase inhibitor (L-NAME (1.0 mg/kg)), and (3) no drug. Design Open-label randomized prospective trial. Participants/Methods These anti-hypotensive agents were administered in random order over three visits in 13 individuals with SCI (T: C3-T4) and six AB controls. Twenty-four-hour hemodynamic data were collected using a portable BP monitor that recorded BP and HR every 20 minutes during the daytime and every 30 minutes during the nighttime. Data were analyzed with a 3 (condition: no drug, midodrine, L-NAME) by 2 (group: SCI, AB) repeated measures analysis of variance. Results There were no significant main or interaction effects for 24-hour SBPavg, DBPavg, HRavg, SBPmin, DBPmin, or HRmin. However, in subjects with SCI, 24-hour SBPmax and DBPmax were significantly increased with midodrine (135 ± 17/90 ± 13) and L-NAME (128 ± 10/84 ± 8) compared to no drug (92 ± 8/53 ± 7; P < 0.0001). In addition, HRmax, was significantly increased after administration of midodrine (88 ± 13 bpm) and L-NAME (97 ± 20 bpm) compared to no drug (55 ± 7 bpm; P < 0.0001) in those with SCI. Three subjects with SCI had hypertensive responses (SBPmax ≥ 140 or DBPmax ≥ 90 mmHg) to both L-NAME and midodrine; an additional four subjects had hypertensive responses to midodrine only, and one subject had a DBPmax in the hypertensive range after L-NAME administration. Conclusion Although average 24-hour hemodynamics were not significantly changed after administration of these anti-hypotensive agents, maximum BP was increased. Qualitatively, there was an increased proportion of hypertensive responses after midodrine than after L-NAME administration. Before these anti-hypotensive medications can be considered safe for long-term use in the SCI population, these hemodynamic responses should be studied in greater detail for extended periods.